Uso dos recursos naturais vegetais na Comunidade Indígena Araçá, Roraima - Perez, Inayê Uiliana (2010)
The use of plant resources by the indigenous communities has two principal components: cultive and extrativism. The extrativism don’t implicate cultive of the resource, caution and replant. The focus of this study is Araçá Community, located at Araçá Indigenous Land, Amajari Municipality, open areas region (Lavrado) of Roraima. The survey has been done by visities in the area where the information has been collected by acquaintance with the dwellers. The aspects that have been analyzed was the use of the cultivated and non cultivated plant resources by the community, the commercialization of these resources, the acquisition of products from outside of the community, agricultural cycle and social aspects involved in the crops. It was related 75 cultivated plants and 88 non cultivated plants entireling 163 plants of 65 different families, Solanaceae is the most frequent with 11 species. The plants have been organized by use categories. The human’s alimentation category is the most important because, besides the larger number of species, the use in this category is most frequent. This category presented more cultivated plants than non cultivated. The categories construction, firewood, religion and workmanship presented just non cultivated plants. Have been related 41 plants commercialized, 33 cultivated and 6 non cultivated. With the money of the commercialization, salaries, and social benefits of the government the indigenous people buy a large variety of industrialized products. The agricultural cultive occurs principally on the forested areas which has the most fertile soils. The technic utilized is the “slash-and-burn agriculture” also known as “swidden cultivation”. The most important crops are manioc, maize, sweet-potato, banana, squash, watermelon, papaya and pepper. The crops are always associated, with at least two plants in the same area. The time of utilization of the area is 2-3 years and the fallow period is 10-15 years. But, can be find areas with more than 20 years that hasn’t been utilized again. The size of the planted areas is between 0,25 to 1,5 hectare. The social aspects about the work division between women, men and children aren’t structured in the community. Doesn’t exist a pattern. This aspects varies family by family. The crops belong to the family, doesn’t exists communitarian crops.